Teaching English Online to Students with Autism Spectrum Disorder and Down Syndrome During the COVID-19 Pandemic - Giraldo Martinez, Zoila Liliana; Ramos Carvajal, Sigrid Andrea (Íkala, Revista de Lenguaje y Cultura, 2021)
The unprecedented reality of the covid-19 pandemic has led students and teachers to adapt to new routines and technological resources so that they can meet the pedagogical requirements generated by this world sanitary emergency. This case study explored a methodological intervention with students from an English school for special needs students in Manizales (Colombia). Our team of two university professors and seven pre-service teachers provided online English lessons to 17 students with autism spectrum disorder (asd) and 13 with Down syndrome (ds). To do it, we used the principles of universal design for learning (udl) and an eclectic method which combines strategies from thre specific approaches: The Presentation, Practice, and Production approach (ppp), the Treatment and Education of Autistic and Related Communication-Handicapped Children (teacch) approach and a behavioral management approach. The purpose of this study was to establish the impact of the implementation of such strategies on the English Language Learning (ell) process of the asd and ds learners. Three data collection techniques, including two surveys to parents and a researcher journal, were used. Findings indicated that: (a) the combination of various stimuli and methodological strategies from a variety of approaches enhanced learning, (b) the use of images and pictograms fostered memory, (c) setting clear routines promoted self-regulation skills, and (d) the families and students’ challenges were turned into opportunities. It was concluded that teaching English online to asd and ds students requires knowledge of their conditions and suitable strategies from an eclectic instructional approach.